Investigating The Use Of The Internet In A Translation Class At Allameh Tabataba'i University, Iran - Vaezian, Helia (2011)
There is no doubt that the Internet is one of the greatest inventions of the 20th century which has had a tremendous impact on our everyday lives. It not only has eased the access of information, but has also provided a new mode of communication across the globe. This valuable source of information has also a lot to offer translators. The present qualitative study aimed at elaborating on the implications and applications of the Internet as a big virtual corpus and as a resource to get texts for inclusion in DIY corpora, in the context of translation of political texts from English into Persian.